Association of stress hyperglycemia ratio with presence and severity of chronic kidney disease among US adults with diabetes mellitus - Lai, Wenguang; Meng, Yaxin; Zhou, Yang; Zhang, Tingting; Zhang, Baoyuan; Huang, Zhidong; Gao, Zhiyong (Frontiers in Endocrinology, 2024)
Background: Among diabetes mellitus (DM) patients, stress hyperglycemia ratio (SHR) is a strong predictor of short-and long-term prognosis, and adverse cardiovascular events. However, whether SHR is associated with increased risk of presence and severity of chronic kidney (CKD) disease remains undetermined.: Patients with DM from the National Health and Nutrition Examination Survey (NHANES) database (1999-2020) were included and divided into 5 groups according to their SHR level (quintile 1 to 5). Study outcomes were CKD, advanced CKD (ACKD), and CKD severity. Logistic regression and restricted cubic spline (RCS)were used to assess the association between the SHR and outcomes.Results: Totally, 6,119 patients were included. After adjustment, compared to patients with SHR in quintile 3 (as reference), the risk of CKD is 1.50 (P<0.001) for quintile 1, 1.23 (P=0.140) for quintile 2, 1.95 (P<0.001) for quintile 4, and 1.79 (P<0.001) for quintile 5. For the risk of ACKD, the OR is 1.46 (P=0.410) for quintile 1, 1.07 (P=0.890) for quintile 2, 3.28 (P=0.030) for quintile 4, and 3.89 (P=0.002) for quintile 5. For the CKD severity, the OR is 1.46 (P<0.001) for quintile 1, 1.20 (P=0.163) for quintile 2, 1.84 (P<0.001) for quintile 4, and 1.83 (P<0.001) for quintile 5. RCS analysis also showed a U-shaped association between SHR and outcomes (All P for nonlinearity<0.05).Our study demonstrated that too low or too high SHR level is significantly associated with adverse renal outcomes in patients with DM.